Strategy-Policy Mismatch How the U.S. Army Can Help Close Gaps in Countering Weapons of Mass Destruction - Bonds, Timothy M. (RAND Corporation, 2014)
Although two successive presidents have determined that weapons of mass destruction (WMD) pose the greatest threat to the American people and have listed countering their proliferation as a top strategic priority, neither administration has followed through by allocating appropriate budgetary resources to it. This report addresses and analyzes the ground force capacity and capabilities needed to perform WMD elimination missions and tasks.